Cerebrovascular disease influences hippocampal subfield atrophy in mild cognitive impairment: Neuroimaging / New imaging methods. (7th December 2020) - Wong, Fennie; Yatawara, Chathuri; Low, Audrey; Wong, Benjamin; Kandiah, Nagaendran
Abstract: Background: Distinguishing between pure AD and AD with concomitant CVD is challenging due to overlapping pathogenesis such as cerebral accumulation of amyloid‐β (Aβ) plaques and neurofibrillary tangles. In recent years, hippocampal subfield volumes have been recommended over other neuroimaging markers of AD due to its functionally distinct nature and higher accuracy. However to date, patterns of hippocampal subfield atrophy in prodromal AD with and without concomitant CVD remain largely unexplored. This study investigates the associations and differences in hippocampal subfield volumes in mild cognitive impairment (MCI) with significant/non‐significant cerebrovascular disease (MCI+/‐CVD). Method: 176 MCI subjects (mean age=65.56 years, SD=8.77) underwent neuropsychological assessments and magnetic resonance imaging. White matter hyperintensities were quantified using modified Fazekas ratings. Subjects with Fazekas ratings of ≥ 8 were categorised as MCI+CVD. Demographics, brain volumetric measurements for grey and white matter volumes, periventricular and deep white matter hyperintensities and hippocampal subfields were examined in MCI+/‐CVD. Multiple linear regressions were conducted for MCI+CVD to examine predictions of hippocampal subfield volumes on cognitive performance. Result: MCI+CVD (N=39) performed worse than MCI‐CVD in all neuropsychological assessments. MCI+CVD had significantly smaller volumes in the hippocampal tail ( p =.042), subiculum (p=.015), CA1 ( p =.023), molecular layer ( p =.009) and fimbria ( p =.025). MCI+CVD had significant associations between hippocampal subfield volumes and cognitive performance: hippocampal tail with global cognition ( p =.049) and visuospatial skills ( p =.004); subiculum with global cognition ( p =.026) and episodic memory ( p =.001), molecular layer with global cognition ( p =.049) and episodic memory ( p =.010) and fimbria with episodic memory ( p =.038). Conclusion: MCI+CVD has significantly greater hippocampal subfield atrophy, with atrophy of the hippocampal tail, subiculum, molecular layer and fimbria correlating to poorer performance in global cognition, visuospatial skills and episodic memory. The findings of this study may guide future research in investigating longitudinal changes in hippocampal atrophy in MCI+/‐CVD and the corresponding implications on cognitive performance.